ANALISIS MANAJEMEN KINERJA SEKOLAH MENENGAH ATAS MUHAMMADIYAH KEBAYORAN BARU BERBASIS DIGITAL DALAM MENINGKATKAN KUALITAS LAYANAN - Naswardi Naswardi (CV. ADIBA AISHA AMIRA, 2024)
Good school performance management will have a significant impact on school progress. The purpose of this study is to determine the extent to which the performance management of the Muhammadiyah Kebayoran Baru school is able to improve the quality of service. The subjects of this study were branch leaders, members of the Dikdasmen council, teachers, and educators who were directly involved in school governance. The data analysis of this study used descriptive qualitative which was able to provide a more comprehensive description of the services provided and their impact on increasing the number of students. The results of the study showed that digital data-based performance management was able to transform school management to be better, structured, and eflective. Schools that are able to provide good service to all students, parents, teachers, and educators will provide comfort during activities at school. The impact is a significant and stable growth in the number of students in the last ten years